Penciptaan Iklim Komunikasi Organisasi (Tinjuan Peran Kepala Dinas Kearsipan dan Perpustakaan Kota Jambi) - Mohamad Muspawi; Firman Firman; Yeni Confristha Manullang (Jurnal Ilmiah Universitas Batanghari Jambi, 2021)
This study aims to determine the steps taken by the head of the department in creating a conducive communication climate in the Jambi City Archives and Library Office and to describe the supporting and inhibiting factors. Using qualitative methods with the type of case study research. The research subjects were the head of the department, the head of the field, employees, cleaning service and security officers. Data collection techniques are interviews. Data analysis techniques are data reduction, data presentation, and drawing conclusions. The results showed that: (1) the steps taken by the head of the service in creating a communication climate when viewed from the dimensions of the communication climate such as support, decision-making participation, trust, openness and candor and the achievement of high performance resulted that the communication climate there was already running conducive overall. However, there are still employees who do not carry out the work given. (2) The supporting factors are the support and motivation of the head of service towards subordinates and preparing the facilities and infrastructure needed in the work. The leaders also monitor and ask about the obstacles they face. The inhibiting factor is the unbalanced number of employees with supervision so that there is often a misunderstanding of perceptions between leaders and employees as well as between employees in the delivery and implementation of tasks, there are employees who do work that is not in accordance with their main duties and responsibilities, and there are also employees who are always reluctant to their leaders and fellow workers which makes communication difficult.